Infectious mononucleosis presenting as abdominal pain (Indian Journal of Case Reports, 2019)
Infectious mononucleosis (IMN) is commonly seen with Epstein-Barr virus (EBV) infection. Severe abdominal pain can occur in IMN due to splenic rupture. However, abdominal pain alone is uncommon in IMN. Here, we report the case of a 42-year old male who presented with IMN induced abdominal pain in the absence of splenic rupture; which is an uncommon scenario.